Pengaruh Economic Value Added, Profitabilitas, Leverage, dan Earning Per Share terhadap Return Saham Pada Perusahaan Oil dan Gas Periode 2011 -2016 - Rd. Qoyyimatul Fitriah W (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This study aims to determine the economic value influence, profitability, leverage, and earnings per share on returns to oil amp; gas period 2011-2016 which is explained systematically about the facts and the nature of an object in the study then merges the variables associated with it with the presentation of secondary data from the financial statements of Oil and Gas companies in Indonesia, the population used in this study the Oil and Gas companies listed on the stock exchange in the period of 2011 to 2016. The samples used in this study were 8 Oil and Gas companies in Indonesia, using the purpose purpose sampling method to obtain representative samples that fit the criteria already confirmed. In this study, the data analysis method used is panel data (pooled data) which is a combination of data between times (time series) and data between individuals or spaces (cross section) in Oil and Gas companies in Indonesia. The results of the study show that Simultaneously or together the independent variables included in this study, namely EVA, ROI, ROA, ROE, DER and EPS affect the return of shares of oil and gas companies in Indonesia. This can be seen from the probability of the F-statistic of 0.00 being below the value of 0.05. Adjusted R square value in this model is 0.366 percent which means that the variation of stock returns which can be explained by the independent variables included in this model is 36.60 percent.